Rapsódia sobre teorias sistémicas do direito (De Legibus - Law Journal, 2022)
The purpose of this study is to provide a brief description of the systemic theories of Law, from its origin to the different intersections with other social and human sciences. In particular, it seeks to (a)critically describe the main features of Luhmann’s and Teubner’s autopoietic socio-legal theories, including their various antisymmetric, transitive and self referential relations, as well as the dialogue it provokes with other apparently similar theses. This paper is intended as the first of two chapters. The second part will consist of the presentation by the author on a new perspective of a systemic view of Law.
Keywords: Systemic Theory; Autopoietic Theory; Law and Society; Philosophy of Law